Penerapan Metode Reward dan Punishment Dalam Meningkatkan Motivasi Belajar Siswa Di SMAN 11 Wajo - Damayanti, Riska; Rosmiati, Rosmiati; Nengsih, Ratika; Bunyamin, Andi; Azhar, Muh (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study investigates how the application of reward and punishment methods on the learning motivation of class XII.4 Islamic Religious Education students at SMA Negeri 11 Wajo. The reward method, in the form of praise and gifts, is given as an appreciation for learning efforts and achievements. The punishment method, which is educational in nature, is applied as a consequence of irresponsible behavior, not as a punishment that is detrimental. The results of the study showed a significant increase in student learning motivation after the method was implemented. This can be seen from the increase in student enthusiasm and enthusiasm for learning. Based on the questionnaire data, student learning motivation increased from 56.67% (pre-cycle) to 61.35% (cycle I) and 75.94% (cycle II). In conclusion, the reward and punishment method has proven effective in increasing student learning motivation in the subject of Islamic Religious Education in class XII.4 SMA Negeri 11 Wajo.